Influence of coarse recycled concrete aggregate on the drying shrinkage of opc concrete / Ahmad Ruslan Mohd. Ridzuan ... [et al.] - Mohd Ridzuan, Ahmad Ruslan; Jelani, Mohd Ali; Mohamad Diah, Abu Bakar; Kamarulzaman, Kamarul Badlishah (2002)
The effects of using crushed waste concrete as coarse aggregates upon deformation due to drying shrinkage of concrete were investigated. Waste concrete cubes which has been tested for compressive strength as a compliance with construction specification were crushed and utilized as coarse recycled concrete aggregates in new concrete. To simulate the real life condition waste concrete with very minimal information about its originality was used in its natural moisture condition. The recycled concrete aggregates were tested for grading, specific gravity, bulk density, impact and crushing value, and water absorption and the results compared with those for natural aggregates. Concrete mix of designed strength 30,35, and 40 N/mm2 at 28 days were prepared by fully replacing the coarse natural aggregate with coarse recycled concrete aggregate and tested. The ultimate drying shrinkage of OPC concrete containing coarse recycled aggregates shows lower or comparable shrinkage to corresponding OPC concrete.